Measuring regional transport sustainability using super-efficiency SBM-DEA with weighting preference. (1st January 2020) - Tian, Na; Tang, Shusong; Che, Ada; Wu, Peng
Abstract: The development of transportation sector promotes China's rapid economic growth, but also brings a negative impact to China's society and environment such as pollution and energy waste. However, limited attention has been paid to China's transportation system, especially in terms of transport sustainability evaluation at a regional level. In this study, we first propose a new indicator system that involves systematic, economic, social and environmental indicators for measuring regional transport sustainability. Then, we propose an improved super-efficiency slacks-based measure DEA (SBM-DEA) model with weighting preference to evaluate the regional transport sustainability efficiency. An empirical application to measuring transport sustainability in Shaanxi province, China, during the period of 2000–2015 is presented to show the effectiveness of the proposed model. The empirical results show that Shaanxi's transport sustainability over half of the years is inefficient and its main reason is that the efficiency of environmental and social dimensions is low. Compared the result with that obtained by the SBM-DEA model without weighting preference, the number of effective decision-making units is reduced by the proposed DEA model. Computational results show that the evaluation result is generally in line with the reality.